2005
DOI: 10.1002/jcu.20151
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic findings of prenatal torsion of ovarian lymphangioma

Abstract: Ovarian cysts are primarily of follicular origin, and ovarian lymphangioma is an extremely rare lesion. Most ovarian cysts demonstrated on prenatal sonograms are asymptomatic and resolve antenatally. We report a case of ovarian torsion in utero secondary to an ovarian lymphangioma in which sonographic examination revealed a changing pattern of the cystic ovarian mass from an anechoic to echogenic appearance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Mesenteric, omental and urachal cysts, duplication anomalies, structures or anomalies leading to intestinal or urinary obstruction such as renal cysts, cystic meconium peritonitis, hydrometrocolpos, duodenal atresia, as well as anterior meningocele should be considered in the differential diagnosis of a cystic abdominal mass in a female fetus. Malignant tumors are rare in the neonatal period, but benign cystic teratomas are the most common ovarian tumors (11, 14, 15, 16, 19). Lymphangiomas also are counted among the hamartomatous lesions of the fetal-neonatal ovary (16, 19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mesenteric, omental and urachal cysts, duplication anomalies, structures or anomalies leading to intestinal or urinary obstruction such as renal cysts, cystic meconium peritonitis, hydrometrocolpos, duodenal atresia, as well as anterior meningocele should be considered in the differential diagnosis of a cystic abdominal mass in a female fetus. Malignant tumors are rare in the neonatal period, but benign cystic teratomas are the most common ovarian tumors (11, 14, 15, 16, 19). Lymphangiomas also are counted among the hamartomatous lesions of the fetal-neonatal ovary (16, 19).…”
Section: Discussionmentioning
confidence: 99%
“…Malignant tumors are rare in the neonatal period, but benign cystic teratomas are the most common ovarian tumors (11, 14, 15, 16, 19). Lymphangiomas also are counted among the hamartomatous lesions of the fetal-neonatal ovary (16, 19). …”
Section: Discussionmentioning
confidence: 99%
“…It was first described in 1908 and as of 2009, about 19 cases have been reported in the literature. 4,5 Only one neonatal case was reported. 5 The histogenesis of this tumor is uncertain and controversial, because the tumor is usually silent and is encountered incidentally, for example, via surgery and biopsy.…”
Section: Discussionmentioning
confidence: 95%
“…4,5 Only one neonatal case was reported. 5 The histogenesis of this tumor is uncertain and controversial, because the tumor is usually silent and is encountered incidentally, for example, via surgery and biopsy. 4 Because of its rarity and lack of specific imaging findings, the diagnosis of ovarian lymphangioma is difficult to make sonographically.…”
Section: Discussionmentioning
confidence: 95%
“…11 A case of ovarian torsion in utero secondary to an ovarian lymphangioma has been reported and laparotomy was performed on the infant after 11 days of life. 20 A case of ovarian cystic lymphangioma in a 72 year old post-menopausal women which was managed laproscopically has also been reported. 21 Aristizabal et al reported a case of lymphangioma that rapidly recurred and spread into adjacent and distant peritoneal organs following oophorectomy.…”
Section: Discussionmentioning
confidence: 99%